2021
DOI: 10.3390/nu13072141
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Salt-Related Knowledge and Behaviors Status of WeChat Users between 2019 and 2020

Abstract: In order to identify the status of salt-related knowledge and behavior of the residents who were active in WeChat software between 2019 and 2020, 10-day salt-related surveys were conducted in 2019 and 2020 based on the WeChat public platform of China Healthy Lifestyle for All Campaign. Distribution and scores of salt-related knowledge, salt reduction behavior and high-salt intake behavior between 2019 and 2020 were compared. Data of 2109 participants in 2019 and 12732 participants in 2020 were left for analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Overall, 27.6% (n = 52) of participants reported they consumed pickles, soya sauce and bean paste, which were high in salt content, as additional seasoning at the dining table. This percentage of adding seasoning at the table was lower than the finding (31.4%) of a study conducted by Yang, Wang [ 46 ] in China but significantly lower than the finding (73%) from an Argentinian study [ 47 ].…”
Section: Discussioncontrasting
confidence: 75%
“…Overall, 27.6% (n = 52) of participants reported they consumed pickles, soya sauce and bean paste, which were high in salt content, as additional seasoning at the dining table. This percentage of adding seasoning at the table was lower than the finding (31.4%) of a study conducted by Yang, Wang [ 46 ] in China but significantly lower than the finding (73%) from an Argentinian study [ 47 ].…”
Section: Discussioncontrasting
confidence: 75%
“…This finding may have resulted from women being assigned additional responsibilities for cooking and diet decisions in society. In fact, in most Chinese households, women take on the role of cooking, and they have a greater focus on healthy diet knowledge, such as salt intake levels [ 39 ]. Accordingly, they may pay extra attention to the healthy diets of family members and possess further diet knowledge and skills.…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggested that women were more motivated to reduce their salt intake, possibly because they were typically in charge of the kitchen and were concerned about their family members' diets, thereby paying more attention to salt-related information ( 16 , 17 ). The results of previous studies were generally supported by the higher awareness of salt reduction behavior rates among the more educated and older adults ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%